하이브리드(CW Nd : YAG Laser+MIG) 용접을 이용한 A5052-H32 맞대기 용접부의 역학적 특성에 관한 연구 - 김준형(Jun-Hyung Kim); 방한서(Han-Sur Bang); 엠.에스.비죠이(M.S. Bijoy); 전근홍(Geun-Hong Jeon); 유재선(Jea-Sun You); 방희선(Hee-Seon Bang) (Han-guk haeyang gonghak hoeji (Online), 2010)
Recently, the application of aluminum alloys has been increasing for lightweight and high quality transport vehicles. Therefore, the proposal has been made to apply high speed hybrid welding methods to the marine grade aluminum alloy (A5052) used for shipbuilding by combining a 3-KW CW Nd : YAG laser and the MIG welding process. In this study, the characteristics of the welding parameters were investigated for a hybrid butt joint. This paper also describes the determination of the heat distribution in a weldment and the welding residual stress using a finite element method. Mechanical experimentation was also used to ascertain the reliability of the weldment.